Livestock Innovation System: Reinventing public research and extension system in India - CHANDER, MAHESH; RATHOD, PRAKASH KUMAR (The Indian Journal of Animal Sciences, 2015)
Innovations in livestock sector are needed as in any other sector, thus, continuously generated globally to increase livestock productivity and improve food security. Most of the research results, research and development outcomes and recommended innovations concerning livestock sector, however, remained confined to the laboratories and libraries in many countries including India. Hence, for effective generation and transfer of innovations, there is a need to gear-up the linkages between technology generation (research), technology dissemination (extension), technology users (farmers’) and support mechanisms (inputs supply, market credit etc) and form a networking system among all the stakeholders leading to innovation system, which is dynamic in nature. To this end, the authors have focused on the concept of Livestock Innovation System (LIS) on the lines of Agricultural Innovation System (AIS), emphasizing on the idea that innovations come from multi-stakeholders like researchers, practitioners, innovative farmers etc. Among various multi-stakeholders, public research and extension system is a major policy instrument for promoting generation and transfer of innovations in majority of the countries in the world including India. This paper has reviewed public research and extension system in India in an effort to make a case for LIS with lessons drawn from select developed countries. It highlights the existing livestock research and extension system, challenges faced and future strategies for improving livestock productivity in India.